DEVELOPMENT OF THE TECHNIQUE FOR IDENTIFYING Z-PREPARATIONS IN BIOLOGICAL OBJECTS BY THE METHOD OF UV-SPECTROPHOTOMETRY - G. P. Chepurnaya; V. A. Kartashov; L. V. Chernova (Разработка и регистрация лекарственных средств)
In the given article, the technique is described and the experimental data for identifying Zaleplon, Zolpidem and Zopiclone (Z-preparations) by method of UV - spectrophotometry isolated from liver tissue are determined. The isolation of Z-preparations was carried out with one of amphiphilic solvents - acetone; purification of impurities - by H-hexane extraction from an acidic medium; TLC was used for additional purification. The Z-preparations were identified by the sequential application of TLC screening and UV-spectrophotometry. The UV-spectrophotometric method was used to determine the quantitative content of the analysis substances. The parameters and validation characteristics of the method were determined, both in the study of native Z-preparations and those isolated from biological objects (linearity, specificity, robustness, and detection limits).